A Study to Assess the Effectiveness of Self Instructional Module on Knowledge Regarding Management of Selected Minor Ailments of Preschool Children among Anganwadi Workers - Kavita J. Gomase; Pradnya Sakle; Pranali Bhoyar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Child healthy development is an investment in the growth and prosperity of the country. Asan opportunity for the future, the value of maintaining child safety can not be overlooked. Most countries’advances have yielded nothing because this dimension was over-looked. An active and successful populationcannot develop from unhealthy children chronically affected by recurrent minor ailments.Objectives:1.To assess the knowledge regarding management of selected minor ailments of preschool children amongAnganwadi Workers.2. To assess the effectiveness of self instructional module on knowledge regardingmanagement of selected minor ailments of preschool children among Anganwadi Workers.3. To associatethe post test knowledge score with selected demographic variables. Materials and Method: This researchwas based on the design of Pre experimental one-group pre-test post-test study. This research examined 100anganwadi workers. This research has attempted at various centers in Anganwadi. The sampling techniqueused in this study was a sampling technique intended for non probability. The data were obtained usingstructured questionnaire. Results: In the post-test 1(1 percent) of the women had very good knowledge andonly 99(99 percent) of them had excellent knowledge score. The minimum score in the posttest was 20 andthe highest score was 25, the mean score for the posttest was 24.05±0.892 with an average percentage scoreof 96.2 percent. Conclusion: The results of this study indicate that the post-test workers at Anganwadi hadexcellent knowledge. The post-test score was significantly higher at 0.05 than the pre-test score. Thus it washypothesized that SIM as a teaching tool was found to be effective in addressing selected minor ailments.